184African Journal of Education, Science and Technology, December, 2017, Vol.4, No.2Effect of Formulated Concentrate Feeding Level on Milk Yield and Quality among Lactating Friesian Cows - Yator , Monica (African Journal of Education,Science and Technology (AJEST), 2017)
Dairy cattle hold enormous significance to humans as they convert energy stored in indigestible plant mass into milk and meat which are digestible and consumed by man. The dairy sub-sector contributes substantially to the 25% of the GDP from Agricultural sector in Kenya. The most important feature of the sub-sector is its change from large to small scale production features, which constitutes two thirds of total dairy herd. Feeding is an important component of keeping milk production at optimum level. The objective of the current study was to evaluate the effect of allocating different supplementary levels of formulated diet on milk production and composition among five lactating Holstein Friesians. The cows were fed on chopped Napier grass as a basal diet and supplemented with 0, 0.5, 0.75, 1.0, and 1.25 kg/litre of milk produced/cow/day of the formulated diet as treatment 1, 2, 3, 4 and 5 respectively. The formulated diet contained the following ingredients, Male maize line grains, molasses, sunflower husk, soya bean meal, rejected beans, milling maize chaff, cotton seed cake, limestone, dicalcium Phosphate (DCP) and dairy Premix. A sub-sample of the formulated diet was collected and analyzed for, DM, CP, NDF, ADF and Ash. The cows under experiment received a mineral supplement of 100g/day, and clean water provided adlib. Milk yields were taken daily and analyzed for Composition. The milk yields were 4.40, 5.1, 5.70, 6.54, and 7.30L/day for treatment 1, 2, 3, 4 and 5 respectively. There were highly significant (p<0.001) differences in milk yields on supplementation levels where 66% increase in milk yield was found at 1.25 kg of supplementation. There was no significant difference in milk composition for all treatment levels of the formulated diet. From this study, it was concluded that formulated ration can be used to improve milk production of dairy animals.